Se me olvido - Mayer, Mercer, 1943- (Racine, Wis. : Western Pub. Co., 1994)
Although children remember to do some things,they don't remember everything that they are supposed to do.
"A Golden book, New York."
"Mercer Mayer's Little Critter"--P. [4] of cover.
Keywords: Memory -- Juvenile fiction; Spanish language materials